Relationship between volume of leukoaraiosis spot and degree of tissue damage: a quantitative diffusion tensor imaging study - Nur Hartini Mohd Taib,; Wan Ahmad Kamil Wan Abdullah,; Ibrahim Lutfi Shuaib,; Muhammad Nur Salihin Yusoff,; Enrico Magosso,; Suzana Mat Isa,; Ahmad Hadif Zaidin Samsudin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Diffusion tensor imaging (DTI) offers parameter indices, namely, mean diffusivity (MD) and fractional anisotropy (FA). Leukoaraiosis is a brain white matter hyperintensity as observed on fluid-attenuated inversion recovery (FLAIR) images. In this study, we attempt to assess leukoaraiosis at its specific spot using a new parameter, namely, lesion-to-normal appearing white matter ratio (LNR). LNR was then used to investigate the relationship between the volume of leukoaraiosis spot and the degree of tissue damage. This study involved 49 leukoaraiosis subjects who altogether contributed to 274 leukoaraiosis spots. The MD, FA, and volume were measured at each spot. LNR was calculated by comparing the MD values of the spot with those of the surrounding normal-appearing white matter (NAWM). The correlation between MD, FA, and LNR with leukoaraiosis volume was then analysed. The leukoaraiosis tissues generally exhibited higher MD (103.97 ± 12.32 × 10-5 mm2/s) and lower FA (0.31 ± 0.08) values than the NAWM tissues (79.30 ± 4.76 × 10-5 mm2/s and 0.41 ± 0.09, respectively). LNR values were found to range from 0.04 to 1.63. The results showed an insignificant association between the leukoaraiosis volume and LNR [r = −.055, p = .368], whereas a very weak association was shown with MD [r = −.196,p =.001] and FA [r = .268, p < .001]. The volume of the leukoaraiosis spot does not necessarily indicate the degree of tissue damage. By using LNR instead of MD, an accurate analysis was performed since the variability of MD for NAWM surrounding the lesion is taken into account.